Photosensitizer effect in Aeromonas salmonicida lipids - Gonçalves, José Manuel Carita (2015)
Photodynamic inactivation is a simple and effective method to destroy microorganism. PDI combines the use of light with a photosensitizer, as porphyrins, which in the presence of oxygen, leads to the formation of reactive oxygen species, such as singlet oxygen and free radicals, capable to oxidize vital membrane structures. The key advantages of Photodynamic Therapy (PDI) are the efficacy in bacteria, fungi, yeasts and protozoa; the low level of resistance induction; and the use of a cheap light source. It is fundamental to understand the importance of cell targets to better understand the photooxidation process. Lipids are important membrane components in bacteria. The main goal of this study was to evaluate the charge effect of four porphyrin derivatives used as photosensitizers in PDI in the photo-oxidation of membrane lipids of Aeromonas salmonicida and relate with the inactivation of this bacterium. The goal was achieved by quantification of lipid hydroperoxides by FOX II method, fatty acid profiles analysis by GC-FID and viability assays; in different periods of light exposure. After PDI it was observed formation of lipid hydroperoxides, changes in the fatty acids profile and a decrease on cell survival. However the results are dependent on the porphyrin used. According to these results, the photooxidation is not directly proportional with the number of charges in the photosensitizers, as other studies had been reported. A direct relation between the photo-oxidation of membrane lipids with the photo-inactivation in the studied bacterium was observed and an order of effectiveness was established. This study reinforces that cationic porphyrins are effective to inactivate bacteria and the importance and efficiency of photodynamic inactivation, as a viable alternative to traditional procedures.